Effect of planting periods on production potential of potato (Solanum tuberosum) varieties under aeroponics - SHARMA, ASHWANI K; BUCKSETH, TANUJA; SINGH, R K (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted during 2017–18 in the aeroponic unit of ICAR-Central Potato Research Institute inShimla, Himachal Pradesh, to evaluate 3 potato (Solanum tuberosum L.) cultivar’s, viz. Kufri Mohan, Kufri Lauvkarand Kufri Himalini growth and production behaviour under 2 different planting periods spaced 10 days apart duringthe autumnal season. The yield per plant and the total number of mini-tubers were shown to be strongly impactedby the planting season as well as the cultivar, according to the findings. The average number of tubers harvested was 32.7/plant in early (10th September) planting as against 21.2 mini-tubers/plant in late (20th September). Similarly, yield per plant was significantly higher (67.67 g/plant) with early planting than with late planting (35.99 g/plant). The production behaviour of the potato varieties under consideration varied significantly. The maximum yield/plant and mini-tuber numbers were recorded in Kufri Lauvkar (34.17 and 73.12 g/plant, respectively), which were significantly higher than the remaining 2 cultivars, which were statistically at par for both the number of yield/plant and minitubers. A delay in the planting of 10 days under aeroponics results in a significant reduction not only in the vigour of plants but subsequently in the number as well as weight of mini-tubers harvested. Thus, for attaining higher rates of multiplication under aeroponics during the autumn season, planting should not be delayed beyond 10th September in a hilly temperate wet zone.